Protagonismo e práticas juvenis de resistência social - Fonseca, Maria de Fátima da (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
Analysis of the juvenile situation in different social places. The young people are presented as the protagonists in the perspective of building a concept in our society which representations of this segment are full of vulnerability and repression to its difference. The text has as reference the publication of Secretaria General de la Organización Iberoamericana de Juventud (OIJ) and intends to unquiet researchers of young people, aiming to create a critical view about this issue, searching to enlarge discussions in order to construct and strength the studies in this area.